Tunneling and other engineering works in volcanic environments: Sousaki and Thessaly - Tsatsanifos, C.; Kontogianni, V.; Stiros, S. (Bulletin of the Geological Society of Greece, 2007)
This study is inspired by the impacts on a tunnel of the Sousaki volcano, in the vicinity of Corinth and examines possible impacts of the Quaternary volcanism on major engineering works in Thessaly. The Sousaki volcano, at the NW edge of the Aegean Volcanic Arc has been associated with important volcanic activity in the past, but its current activity is confined to géothermie phenomena. A tunnel for the new Athens-Corinth High Speed Rail was excavated through the solfatara of the volcano, an area characterized by numerous faults and physical cavities. High temperatures and geothermal gases released in the underground opening through the faults caused disturbance to the tunnel construction, need for supplementary investigations and adoption of special measures to maintain tunnel stability. Experience from the tunnel at Sousaki indicates that similar risks may be faced in future major engineering works in other regions of Greece. Such an example is the area of Microthives and Achillio, Magnesia, Thessaly. Tunnels for the new highway and railway networks constructed or planned through at least two volcanic domes and other main engineering works may also face volcano-associated effects. Optimization of the network routes in combination with special construction techniques and safety measures need to be followed for minimization of such volcanic risks.